(untitled) (Práxis Educativa, 2009)
This paper discusses two concepts of research used to develop policies: “policy sciences” and “evidence-based education”. To this end, the repercussion of these proposals in education in other countries and their repercussions in the Brazilian context are analyzed and considered. Furthermore, there is an attempt to emphasize the characteristics of educational research starting in Brazil from 1950 and 1990. The comparison between international and local repercussions of “policy sciences” and “evidence-based education” suggests some reflections about the production and the use of scientific knowledge that aims to contribute to the discussions about the social impact of research on education in Brazil. Keywords: Educational research. Policy sciences. Evidence.